Pomelo (Citrus maxima) Peel Ethanolic Extract Mitigates Isoniazid–Rifampicin–Induced Hepatotoxicity in a Male Wistar Rat Model - Luna Raisya Azalia; Sabrina Dewi Anggraeni; Arin Tentrem Mawati (STIKep PPNI Jawa Barat, 2026)
Background: Tuberculosis continues to pose a substantial public health challenge in Indonesia, which currently ranks second worldwide in disease burden. Although first-line antituberculosis drugs such as isoniazid and rifampicin are highly effective, their prolonged use is frequently associated with hepatotoxicity, which may disrupt treatment continuity and compromise patient safety. Identifying adjunctive strategies capable of reducing liver injury during antituberculosis therapy therefore remains an important research priority. Objective: This study aimed to examine the concurrent hepatoprotective effect of pomelo (Citrus maxima) peel ethanolic extract in a male Wistar rat model exposed to isoniazid–rifampicin–induced liver injury. Methods: An experimental posttest-only control group design was applied using thirty-two male Wistar rats distributed into five groups: a normal control, a negative control receiving isoniazid and rifampicin, and three treatment groups administered pomelo peel ethanolic extract at doses of 100, 200, and 400 mg/kg body weight. Hepatotoxicity was induced with isoniazid and rifampicin, followed by extract administration two hours after drug exposure from day 4 to day 10. Liver function was assessed by measuring serum alanine aminotransferase (SGPT) and aspartate aminotransferase (SGOT). Phytochemical screening was conducted to identify major secondary metabolites present in the extract. Results: Phytochemical analysis revealed the presence of flavonoids, tannins, alkaloids, triterpenoids, and quinones in pomelo peel extract. Rats receiving isoniazid–rifampicin exhibited marked elevations in SGPT and SGOT levels compared with the normal control group. Concurrent administration of pomelo peel extract significantly reduced these enzyme levels across all treatment doses relative to the negative control. The 400 mg/kg body weight dose produced the greatest attenuation of hepatic enzyme elevation, indicating a dose-related protective response. Conclusion: Pomelo (Citrus maxima) peel ethanolic extract demonstrates dose-dependent hepatoprotective activity during concurrent exposure to isoniazid and rifampicin in male Wistar rats. These findings suggest that pomelo peel extract may have potential as a supportive agent to mitigate antituberculosis drug–induced liver injury, although further mechanistic, pharmacokinetic, and clinical investigations are required prior to translational application